De mari Aegaeo ad Siciliae litora sito (Luc. Phars. II, 665) - Vetushko-Kalevich, Arsenius (Hyperboreus, 2013)
Describing Caesar’s attempts to keep Pompey from leaving Brundisium’s harbour with the help of masonry and rocks, Lucan compares this useless work with throwing mount Eryx into the Aegean sea and Gaurus into the lake Avernus (2, 665–668). The former is most surprizing. Editors that retain the reading of the manuscripts either interpret Aegaei as a designation of a deep sea in general or incriminate to Lucan a geographical error. The most popular emendation is Bentley’s Aeolii, supported by Housman. The author defends Burmann’s proposal that the “Aegean sea” refers to a part of the Mediterranean near the Aegadian islands to the north of Sicily. In general, Lucan is rather bold in forming geographical epithets, cf. Perseus in the sense of Persicus in 6, 449. Moreover, there is another passage in the Pharsalia, where mare Aegaeum arguably stands for the “Aegadian” sea, viz. 5, 612–614: thus the Tyrrhenian sea migrated to “Aegadian” would be geographically symmetrical to the following conﬂict of the Ionian and the Adriatic seas.